ANALISIS LUAS BANGUNAN DAN FAKTOR SEKUNDER PENENTU KENYAMANAN RUMAH TINGGAL SEDERHANA - Hatta Musthafa Adham Putra; Bhanu Rizfa Hakim (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract: Demand of simple housing is growing rapidly as the population increases. Especially for simple housing for residents who run the National Family Planning Program. In principle, a house is not only a place of shelter but a place for various activities of each individual resident of the house so that it will be related to the ideal area. The simple residence has an area of 21 sqm, 36 sqm, 45 sqm and 60 sqm. A certain area of residence will affect the comfort level of residents in their activities. The research will use qualitative and quantitative descriptive methods in analyzing the comfort level of the area to the comfort level of the occupants in activities as seen from the size, shape and function of the space. This research will produce the ideal house area for residents of the Family Planning Program, as well as external factors that affect the comfort of the house.Abstrak: Kebutuhan rumah tinggal sederhana berkembang pesat seiring bertambahnya jumlah penduduk. Khususnya kebutuhan rumah sederhana bagi penghuni yang menjalankan Program Keluarga Berencana Nasional. Rumah tinggal pada prinsipnya bukan hanya menjadi tempat bernaung melainkan sebagai wadah untuk berbagai aktifitas setiap individu penghuni rumah sehingga akan berkaitan dengan luasan ideal. Rumah tinggal sederhana memiliki luasan dari 21 m2, 36 m2, 45 m2, dan 60 m2. Luasan rumah tinggal tertentu akan mempengaruhi tingkat kenyamanan penghuni dalam beraktifitas. Penelitian akan menggunakan metode deskriftif kualitatif dan kuantitatif dalam menganalisa tingkat kenyamanan luasan terhadap tingkat kenyaman penghuni dalam beraktifitas yang dilihat dari luasan, bentuk, dan fungsi-fungsi ruang. Penelitian akan menghasilkan luasan rumah ideal bagi penghuni Program Keluarga Berencana, serta faktor-faktor eksternal yang berpengaruh terhadap kenyamanan rumah tinggal.